1979
DOI: 10.1128/aac.16.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and nature of intracellular alpha-aminoadipic acid-containing peptides from Paecilomyces persicinus P-10

Abstract: Small intracellular peptides containing a-aminoadipic acid, cysteine, and a valine moiety were obtained from mycelia of Paecilomyces persicinus P-10 by ethanol or trichloroacetic acid extraction. After performic acid oxidation and ionexchange chromatography, analysis of the peptide fractions by two-dimensional thin-layer electrophoresis and chromatography revealed the presence of three related peptides, as sulfonic acid derivatives, each containing a-aminoadipic acid. Each peptide was isolated in chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…in Acremonium and Cephaloporium genera as well (W. Gams, personal communications). The production of CPC in A. persicinum has shown to be 5 -8 mg/dl by Eriquez andMalowitz studies (Eriquez andPisano, 1979 andMalowitz, 1982), which was confirmed in this study to be 5 mg/dl (data not shown). Therefore, A. persicinum has not been applied for biotechnological processes due to its low CPC production.…”
Section: Discussionsupporting
confidence: 84%
“…in Acremonium and Cephaloporium genera as well (W. Gams, personal communications). The production of CPC in A. persicinum has shown to be 5 -8 mg/dl by Eriquez andMalowitz studies (Eriquez andPisano, 1979 andMalowitz, 1982), which was confirmed in this study to be 5 mg/dl (data not shown). Therefore, A. persicinum has not been applied for biotechnological processes due to its low CPC production.…”
Section: Discussionsupporting
confidence: 84%
“…Cephalosporin C is a 13-lactam antibiotic formed in Cephalosporium acremonium (Acremonium chrysogenum; the name C. acremonium is used here to avoid confusion between Penicillium chrysogenum and A. chrysogenum) and other filamentous fungi by condensation of L-a-aminoadipic acid, L-cysteine, and L-valine (11,12). The first step in the cephalosporin-biosynthetic pathway involves a complex set of biochemical reactions ( Fig.…”
mentioning
confidence: 99%
“…The presence of nonribosomal peptides in the culture of the penicillin or cephalosporin producers P. chrysogenum, Acremonium chrysogenum, and Paecilomyces persicinus (8,23) that are secreted into the culture broth (24) led us to study if these peptides or another secreted small molecule serves to induce penicillin biosynthesis.…”
mentioning
confidence: 99%